2016
DOI: 10.18632/oncotarget.8080
|View full text |Cite
|
Sign up to set email alerts
|

Driver or passenger effects of augmented c-Myc and Cdc20 in gliomagenesis

Abstract: PurposeCdc20 and c-Myc are commonly overexpressed in a broad spectrum of cancers, including glioblastoma (GBM). Despite this clear association, whether c-Myc and Cdc20 overexpression is a driver or passenger event in gliomagenesis remains unclear.ResultsBoth c-Myc and Cdc20 induced the proliferation of primary glial progenitor cells. c-Myc also promoted the formation of soft agar anchorage-independent colonies. In the RCAS/Ntv-a glia-specific transgenic mouse model, c-Myc increased the GBM incidence from 19.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…It was reported that CDC20 was a critical regulator of tumor-initiating cell proliferation and survival of glioblastoma cells (35). Combining the findings of other studies, CDC20 was found to play a role in cell cycle progression, apoptosis and brain development, and these findings indicated that it may be a potential novel target for therapeutic intervention in brain tumors, particularly MB (36,37). In addition, the RNA levels of CDC20 and MAD2L1 were associated with glioma grade, which suggested a clinical benefit as a biomarker (38).…”
Section: Discussionsupporting
confidence: 60%
“…It was reported that CDC20 was a critical regulator of tumor-initiating cell proliferation and survival of glioblastoma cells (35). Combining the findings of other studies, CDC20 was found to play a role in cell cycle progression, apoptosis and brain development, and these findings indicated that it may be a potential novel target for therapeutic intervention in brain tumors, particularly MB (36,37). In addition, the RNA levels of CDC20 and MAD2L1 were associated with glioma grade, which suggested a clinical benefit as a biomarker (38).…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, using an orthotopic xenograft model overexpression of Cdc20 enhanced the GSCs to generate brain tumors, whereas depletion of Cdc20 retarded the GSCs to develop brain tumors [ 39 ]. Strikingly, it has been reported that Cdc20 induced the proliferation of primary glial progenitor cells [ 40 ]. Some studies showed that rottlerin inhibited cancer cell growth and induced apoptosis in a variety of human cancers [ 13 , 14 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its role as methyltransferase, EZH2 acts as a major suppressor of tumor suppressor expression such as p19, p57, and E‐cadherin . Protein kinase B (AKT) is an oncogenic kinase that interferes with cellular transformation, angiogenesis, invasion, and migration in tumor cells . Overexpression of AKT significantly increases at the level of EZH2 S21 phosphorylation .…”
Section: Effects Of Melatonin On Signaling Pathwaysmentioning
confidence: 99%
“…One major challenge in the development of new therapies is the heterogeneity of tumor at the cellular and molecular levels . Multiple studies indicated excessive expression of a large number of possible oncogenes in GBM . The main goal of cancer treatment is to find new biomarkers that can suppress cancer cells without damaging normal cells .…”
Section: Introductionmentioning
confidence: 99%